Keputusan pembelian: Jalinan antara media cetak, media atas talian dan media bersemuka - Mohamad, Noraihan; Ishak, Mohd Sobhi; Mohd Rashid, Sabrina (Universiti Kebangsaan Malaysia, 2016)
Consumer buying decisions on a product can be influenced by a variety of things such as advertising, media and environmental factors.From the media perspective, consumer buying decisions do not just rely on the information derived from one media only.But, the tendency to reduce the risks in buying will encourage users to build up a better understanding about the product. Thus, based on the Media Richness Theory, this study aimed to identify the influence of the link of print media, online media and face-to-face media to strengthen of consumer understanding about the product that ultimately affect their purchasing decisions.This study focuses on flyers, social media, friends, other stores and stores of choice as the media that linked by a consumer to clarify their uncertainty about the computing product price, functionality, quality, brand, assurance and design. A cross-sectional survey conducted on education institution community in the state of Kedah and Perlis.A total of 150 questionnaires were distributed in field studies.A total of 115 data was collected and analyzed using the SPSS version 19.The study found that online media is the first source of information about products but not in terms of making decisions.Meanwhile, friends and stores of choice are complementary source of information to consumers to enhance their understanding about the products before making a buying decision.In conclusion, a combination of friends and stores of choice are the media that influenced the consumers’ buying making decision process towards computing products.